Architectural Renewal And Retrofit Design Of Rural Primary School Learning Space In Jiangsu Province, China - Jiang, Baiyu (2025)
This study addresses the need to adapt rural primary school learning spaces in China to support the transition from traditional lecture-based teaching to diverse teaching and learning (TnL) activities in line with UNESCO’s Sustainable Development Goal 4 and China’s Educational Reform. Focusing on rural primary schools in Lianyungang, Jiangsu Province, the research investigates the relationship between learning space design and TnL activities, focusing on spatial layout, physical attributes, technology, and furniture.